Indigenous Insights into Ethical Leadership: A Study of Māori Leaders - Haar, Jarrod (Journal of business ethics, 2019)
The need for ethical leadership in navigating today’s complex, global and competitive organisations has been established. While research has confirmed the importance of ethical leaders in promoting positive organisational and employee outcomes, scant research has examined the antecedents of ethical leadership. Furthermore, there has been a call for further examination of leadership models, particularly indigenous leadership models. Responding to these issues, this study suggests Māori leaders’ values add insights into enhancing ethical leadership. Three studies confirm the role of Māori values and ethical leadership. Study one, based on kaupapa Māori research methods, is an exploratory 22-interview study of Māori leaders and identifies five values, (humility, altruism, long-term orientation, collectivism and cultural authenticity) as common to successful indigenous leaders. In study two, 249 employees rate their leaders on these five dimensions in relation to their ethical leadership and exchange relationships. Structural equation modelling shows strong support for the distinct nature of the five values and their positive influence on ethical leadership perceptions and quality exchange relationships (LMX). Study three, on 122 employees, reinforces the findings of study two—and demonstrates that LMX predicts job outcomes both indirectly and directly, with humility and collectivism also directly predicting outcomes. Our findings suggest that indigenous leaders’ values enhance perceptions and outcomes of ethical leadership for employees.